Analyse Multidimensionelle de la Responsibilite Sociale de la PsychologieN - Lecomte, Conrad; Perron, Jacques (Canadian Journal of Counselling and Psychotherapy, 2012)
Acritical analysis of social involvement of counsellors and psychologists is discussed. Based on a series of studies conducted in the Province of Quebec, the present article provides an articulated analysis of the socio-professional identity of counsellors and psychologists. Four leading questions are explored; 1) What are the characteristics of counsellors and psychologists socio-professional identity? 2) What are the competencies that psychologists and counsellors value? 3) Do counsellors and psychologists perceive themselves as competent professionals in terms of social intervention skills? 4) What is the value system of counsellors and psychologists?